Wild potato species threatened by extinction in the Department of La Paz, Bolivia - Coca Morante, M.=700 1 Castillo Plata, W
Es, En)
Ilus., 13 ref.
Keywords: SOLANUM; ESPECIES EN PELIGRO DE EXTINCION; URBANIZACION; REHABILITACION DE TIERRAS; ESPAÑA; EROSION GENETICA